Pug's sleepover - May, Kyla (2022)
Bub the pug and his human Bella plan a pirate-themed sleepover with their friends and discover that even as the best-laid plans go awry they can still have fun.
Keywords: Human-animal relationships -- Fiction; Sleepovers -- Fiction; Pug -- Fiction; Dogs -- Fiction; Diaries -- Fiction